Effects of Brick Pattern on the Static Behavior of Masonry Vaults. Issue 8 (3rd August 2022) - Boni, Claudio; Ferretti, Daniele; Lenticchia, Erica
ABSTRACT: The design of brick masonry vaults has frequently been one of the main topics of historical construction handbooks, where also the orientation of the blocks was an examined issue. However, the influence of brick-texture has not yet been thoroughly investigated computationally. In the present paper the static behavior of masonry vaults of different shapes (barrel, pavilion, and cross vaults), was studied by analyzing and integrating two points of view: one historical and the other computational. First, the instructions provided by ancient documents were described. Then, a Non-Smooth Contact Dynamics Software was used to model vaults with different brick patterns suggested in the past. The vaults were studied with self-weight to observe load descent. Then, a concentrated force was added up to collapse. The analyses show how the load descent and load-bearing capacity are influenced by the brick pattern. Finally, the results of the various analyses were compared with the insights of the past.